The effects of intrauterine device on cervico-vaginal smears with liquid-based cytology technique: A North-Eastern Anatolia region study in Turkey - Erdogan-Durmus, Senay; Akalp-Ozmen, Sevilay; Calik, Ilknur; Kurt, Ali; Balta, Hilal; Can, Yusuf; Kabalar, Mehmet Esref (Womens Health & Action Research Centre, 2022)
Intrauterine device (IUD), is one of the most efficient methods of contraception. The aim of study to investigate the effects of intrauterine device in cervicovaginal smears with liquid based cytology technique in our patient population. Cervicovaginal smears of 5492 patients who sought the services of the pathology department in a sixmonth period were reviewed retrospectively. Samples were prepared with liquid based cytology technique. The patients using IUD as contraceptive method (n= 562 cases) were included in the study. The samples taken with the conventional method were excluded from the study. The results were categorized according to the Bethesda system. The age range of the patients was 18-61 years (mean age: 34.6). The most common diagnosis was negative for intraepithelial lesion or malignancy (97.2%). In 307 patients (54.6%) there were infection and only in 93 out of them (30.2%) a specific agent was detected. Actinomyces (11%) were recorded as the most common infectious agent, followed by Gardnerella vaginalis (2.8%) and Candida species (2.4%). There were reactive changes in 134 cases (23.8%). In 13 cases (2.3%) epithelial cell abnormalities were detected. The most common cytopathologic diagnosis was ASC-US (atypical squamous cells of undetermined significance) in patients who had epithelial cell abnormalities (2.1%). In conclusion, IUDs increase the frequency of genital infection by disrupting the genital flora. In our study the most frequent agent was Actinomyces, and this rate was higher than some studies. This high rate for Actinomyces may be associated with IUDs that are frequently used for contraception in Erzurum province with long term uses.
Keywords: IUD; cervico-vaginal smear; liquid based cytology; PAP test